Food value chains: Transformations in low- and middle-income countries - Reardon, Thomas; Minten, Bart; Narayanan, Sudha; Swinnen, Johan (International Food Policy Research Institute, 2025)
Food value chains (FVCs) play a critical role in food systems by linking from agricultural input providers to farmers and producers to consumers. Over the past 50 years, the economic, demographic, and policy context of FVCs in low- and middle-income countries has changed enormously. This chapter discusses major phases and revolutions that shaped the growth, structure, and importance of FVCs to economies, employment, and diets, as well as policy research issues and contributions, and looks ahead to key trends that will continue to shape FVCs.